Polityka amortyzacyjna w procesie odtwarzania środków trwałych a czas życia produktu - Goldmann, Katarzyna (The Politic of Depreciation in the Process of Recovery of Fixed Assets and its Connection with the Lifetime of Product, 2005)
One of the most important factors, which influence the proper depreciation politic is taking into consideration the problem of lifetime of products. It is a very important issue in the process of fixed assets recovery. Using the proper method and stating correct depreciations rate in the initial phase of lifetime of the product, and the ability to correct these rates in further stages of products development, enables the enterprise to create depreciation fund. This fund is very useful and helps to recover fixed assets in the future. The questionnaire researches, which main goal was to verify the dependence from the chosen depreciation method has shown, that this choice is independent for most (64,37%) of the respondents.(original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1085, s. 173-185